Toddler with giant omental cyst, profound anemia, and shock: case report and review of the literature - Cheng, Fengchun; Xing, Xueling; Liu, Xiaoming; Sun, Shuai; Lv, Zhaona; Xu, Xiaoliang; Fu, Tingliang; Geng, Lei (Frontiers in Medicine, 2023)
Giant greater omental cysts with associated massive hemorrhage are rare. We encountered a 16-month-old boy with a four-day history of acute abdominal pain, distension, and paleness. Physical examination revealed a blood pressure of 74/27 mmHg. No well-defined masses were observed on abdominal palpation. The hemoglobin level on admission was 24 g/L. After initial resuscitation and blood transfusion, a computed tomography (CT) scan was performed, revealing a giant cystic mass with an intracystic hemorrhage. The diagnosis was confirmed via exploratory laparotomy, and the cyst, with the attached partial omentum was removed. Pathological findings revealed a simple cyst originating from the greater omentum. The patient recovered uneventfully and remained well during the two-year follow-up period. We reviewed the literature published over the last 27 years on cases of omental cysts to evaluate demographic characteristics, clinical presentations, complications, diagnostic tool options, and surgical approaches.